The Change of Knowledge and Attitude of Bride and Groom Candidate After Reproductive Health Pre-Marital Course by KUA Officer (Department of Public Health, Faculty of Sport Science, Universitas Negeri Semarang, 2018)
Reproductive health in Indonesia is still very poor, as evidenced by the still high maternal mortality rate (MMR). MMR decline was slow, as well as in the province of Central Java. The highest is in Brebes Regency which has as many as 53 cases of maternal decease. One of the causes of high MMR is the lack of reproductive health sensitivity of bride and groom candidates. The purpose of this research is to analyze the influence of counseling on bride and groom candidates knowledge and attitude related to reproductive health. This research is a quasi experimental research with pre and post test without control group design. The population was bride and groom candidates listed in KUA of Brebes Regency in July and August of 2017, with a sample of 100 pairs selected according to the inclusion criteria. The interventions in the form of a one-day course by KUA officers on reproductive health with Bride and Groom Candidates Reproductive Healt booklet and flipcharts as the tools. The data of knowledge and attitude are obtained by interviewing the bride and groom candidates. Analysis is conducted with Wilcoxon Match Paired Test. The results showed that there is a difference of bride and groom candidates knowledge and attitude before and after intervention (p 0,05), with mean value increased 2.58 points (knowledge) and 3,21 points (attitude). Recommended advised are the pre-marital program socialized by KUA officers is expanded and multiplication of the booklet as a tool for the officers in pre-marital courses implementation.